Review of the safety, efficacy, costs and patient acceptability of recombinant follicle-stimulating hormone for injection in assisting ovulation induction in infertile women - Marleen Nahuis; Fulco van der Veen; Jur Oosterhuis; et al (Dove Medical Press, 2009)
Marleen Nahuis1,2,3, Fulco van der Veen1, Jur Oosterhuis2, Ben Willem Mol1, Peter Hompes3, Madelon van Wely11Center for Reproductive Medicine, Department of Obstetrics and Gynaecology (H4-205), Academic Medical Center, University of Amsterdam, Amsterdam, The Netherlands; 2Department of Obstetrics and Gynaecology, Medisch Spectrum Twente, Enschede, The Netherlands; 3Department of Obstetrics and Gynaecology, Free Medical University, Amsterdam, The NetherlandsAbstract: Anovulation is a common cause of female subfertility. Treatment of anovulation is aimed at induction of ovulation. In women with clomiphene-citrate resistant WHO group II anovulation, one of the treatment options is ovulation induction with exogenous follicle-stimulating hormone (FSH or follitropin). FSH is derived from urine or is produced as recombinant FSH. Two forms of recombinant FSH are available – follitropin alpha and follitropin beta. To evaluate the efficacy, safety, costs and acceptability of recombinant FSH, we performed a review to compare recombinant FSH with urinary-derived FSH products. Follitropin alpha, beta and urinary FSH products appeared to be equally effective in terms of pregnancy rates. Patient safety was also found to be comparable, as the incidence of side effects including multiple pregnancies was similar for all FSH products. In practice follitropin alpha and beta may be more convenient to use due to the ease of self-administration, but they are also more expensive than the urinary products.Keywords: follitropin apha, follitropin beta, urinary gonadotropins, polycystic ovary syndrome